Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.12706/itea.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Compuestos fenólicos y actividad antioxidante en líneas experimentales de sorgo pigmentado cultivado en Coahuila México

Abstract: El objetivo de este estudio fue evaluar y comparar las características de color, el contenido fenoles totales, flavonoides totales, taninos condensados, antocianinas totales y la capacidad antioxidante de siete líneas experimentales de sorgo pigmentados (color de grano naranja y rojo) cultivados en Coahuila, México. Los resultados revelaron que los valores de luminosidad, la saturación del color y el ángulo de tono (L*, C* y h) se encontraron en un rango de 39 a 64, 14 a 18 y 40 a 80, respectivamente, lo que i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Phenolic compounds in cereals help to protect lipids from the cell membrane against reactive oxygen species, suggesting their use as antioxidants. The results of antioxidant capacity in ABTS are higher than those reported by Hou et al (2016), who when evaluating the antioxidant capacity in sorghum genotypes, found values of 582.70 µmol TE/100 g, but similar to the average value (3,579.69 µmol TE/100 g) reported for pigmented sorghum genotypes (Flores-Naveda et al, 2021). In this study, the antioxidant activity was higher in free phenol extracts than in bound phenol extracts.…”
Section: Antioxidant Capacitysupporting
confidence: 73%
See 2 more Smart Citations
“…Phenolic compounds in cereals help to protect lipids from the cell membrane against reactive oxygen species, suggesting their use as antioxidants. The results of antioxidant capacity in ABTS are higher than those reported by Hou et al (2016), who when evaluating the antioxidant capacity in sorghum genotypes, found values of 582.70 µmol TE/100 g, but similar to the average value (3,579.69 µmol TE/100 g) reported for pigmented sorghum genotypes (Flores-Naveda et al, 2021). In this study, the antioxidant activity was higher in free phenol extracts than in bound phenol extracts.…”
Section: Antioxidant Capacitysupporting
confidence: 73%
“…In the case of GY, the results of this work are similar to those reported by Jabereldar et al (2017), who reported sorghum grain yields of 25.10 to 61.50 g/plant in sorghum genotypes grown in two seasons. At present, sorghum genetic improvement programs are aimed at the development of genotypes with good yields, in addition to a high concentration of nutritional compounds in the grain (Flores-Naveda et al, 2021). The results for DF differ from those obtained by Galicia-Juárez et al (2020), who reported early genotypes with a flowering range of 51 to 71 days, and late genotypes with a range of 72 to 79 days.…”
Section: Agronomic Parametersmentioning
confidence: 78%
See 1 more Smart Citation